The Role Of Neighborhood Identity In Creating The Sense Of Attachment To The Place In The Residents Of The Traditional Residential Fabric Of Tehran (A Case Study On Five Municipal Districts Of Tehran) - Azemati, Saeid; Mansoury, Mansour; Dehkordi, Seyed Saleh Rokni; Mordavan, Ramin; Maghsodi, Mojgan (The Turkish Online Journal of Design Art and Communication, 2016)
In the modern society, it is necessary to consider the neighborhood identity which plays a critical role in socialization and human-orientation of the urban structure. The social events in residential regions of cities which are known as the urban living cells are very determinant in residents’ liveliness. Therefore, the current research studies the neighborhood identity and the sense of attachment in urban residents. This research is a survey study, during which required data were collected using a questionnaire and an interview. After data had been collected and encoded, they were analyzed with statistical softwares. The statistical population of this study includes five municipal districts of Tehran (i.e. Tajrish, Navvab, Moniriyeh, Rahahan and Bahar). Sample size was calculated using the Cochran formula. Thus, 300 people were determined as the statistical population. According to the findings of this study, the age of people is an effective factor on their attachment to their neighborhood identity. Furthermore, those people who are more satisfied with their neighborhood have a stronger attachment to their neighborhood identity and as a result, these neighborhoods are essentially safer. The native inhabitants, compared to the non-natives, have a stronger attachment to the neighborhood identity. Those who have a stronger sense of attachment to the place participate more actively in the activities related to their neighborhood. Residents’ attachment to the neighborhood increases by the increase in the safety of the residential areas. Besides, the satisfaction of the urban performance affects on the attachment to the neighborhood identity. This will be effective on the increase in social interactions and liveliness of these neighborhoods.
Keywords: identity; neighborhood; safety; the sense of attachment to the place; social interactions